Portal Hypertension and Current Endoscopic Management - Robbins, Justin; Mujumdar, Sahaj; Tholey, Danielle M. (Digestive Disease Interventions, 2022)
Portal hypertension is a difficult to treat sequelae of end stage of liver disease, and is associated with a variety of complications. Notably, it can lead to significant gastrointestinal bleeding, which carries a high risk of mortality. Sources of portal hypertensive bleeding include esophageal and gastric varices, portal hypertensive gastropathy and ectopic varices. Fortunately, endoscopic techniques are effective in both prevention and management of acute bleeding, and their application and expansion has led to improved outcomes. Endoscopy plays a pivotal role as it allows for direct visualization and diagnosis as well as immediate intervention. There are several endoscopic techniques available for the treatment of esophageal varices including band ligation, glue therapy and sclerotherapy. There are, however, gray areas within the management of portal hypertensive bleeding such as the management of portal hypertensive gastropathy and gastric variceal bleeding, both of which can be more challenging to treat endoscopically. Thus, there is growing interest regarding how novel advanced therapeutic techniques can address these areas with a focus on endoscopic ultrasound guided therapies. This article will review both traditional and novel endoscopic techniques used in the management and prevention of portal hypertensive associated bleeding.
Keywords: hypertension; portal/complications; hypertension; portal/therapy; esophageal and gastric varices; endoscopy; liver cirrhosis; end stage liver disease